Assessing training needs of the printing industry in Kumasi - Djan, Victor Acquah (2014)
A thesis submitted to the Department of Publishing Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Arts.